Protein‐Losing Gastroenteropathy Associated With Sjögren's Syndrome: First Known Case Reported Outside of Asia. Issue 3 (April 2015) - Gupta, Amit; Cohen, Natalie L.; McCarthy, Sean; McHugh, Jonathan B.; Kwon, Richard
Abstract : N/A: Protein‐losing gastroenteropathy (PLGE) is a rare extraglandular manifestation of Sjögren's syndrome, reported in fewer than 10 cases. We report a 58‐year‐old white woman with Sjögren's syndrome, type 1 renal tubular acidosis, and PLGE, who presented with cachexia and 100‐pound weight loss. The diagnosis was made based on hypoalbuminemia in the absence of significant proteinuria, low levels of fat soluble vitamins, low transferrin, and an elevated alpha‐1 antitrypsin (A1AT) fecal clearance, supported by imaging and endoscopy, with biopsy showing lymphocytic infiltration. She was successfully treated with cyclophosphamide and prednisone. To our knowledge, this is the first such case outside of Asia.